2010
DOI: 10.1677/joe-10-0062
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional and environmental factors affecting plasma ghrelin and leptin levels in rats

Abstract: We examined which factors suppress the rise of ghrelin secretion under hunger in 16-h-starved rats, and compared the responses of plasma ghrelin and leptin levels to various exogenous and endogenous stimuli in intact rats. Although an acute expansion of the stomach by infusion of 6 ml air or 3 ml water in rats starved for 16 h did not change the level of plasma acyl-ghrelin 3 ml corn starch solution, corn oil, or 20% ethanol significantly decreased it. Vagotomy inhibited suppression by nutrients but not by eth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 59 publications
(43 reference statements)
0
15
2
Order By: Relevance
“…Nakahara et al reported that leptin responds in a delayed fashion (>60 min) to acute stress [40] but the data presented in this study along with reports from Patterson-Buckendahl et al suggest that, in the fed state, leptin rises rapidly in response to acute stress and remains elevated throughout stressor exposure [41]. Rats fasted for 24 h, however, failed to demonstrate a leptin response to 10 and/or 100IS (Figure 4(d)).…”
Section: Discussioncontrasting
confidence: 44%
“…Nakahara et al reported that leptin responds in a delayed fashion (>60 min) to acute stress [40] but the data presented in this study along with reports from Patterson-Buckendahl et al suggest that, in the fed state, leptin rises rapidly in response to acute stress and remains elevated throughout stressor exposure [41]. Rats fasted for 24 h, however, failed to demonstrate a leptin response to 10 and/or 100IS (Figure 4(d)).…”
Section: Discussioncontrasting
confidence: 44%
“…Ghrelin has been shown to inhibit insulin secretion in humans19 and ghrelin levels seem to be elevated in fasting conditions 20. Similarly, recent studies have suggested more direct effects of peptide YY on insulin sensitivity,21 but the role of peptide YY independent of food intake still needs to be confirmed.…”
Section: Discussionmentioning
confidence: 99%
“…These differences may be attributed to gene-gene interaction, racial differences, and environmental factors. Also, changes in environmental temperature and stress can affect the expression of leptin [53] and change the risk of breast cancer.…”
Section: Discussionmentioning
confidence: 99%